An Alaskan family found - Carpenter, Beth (Romance novelist) (Harlequin Heartwarming, 2022)
Alaskan peony farmer Caleb DeBoer can barely keep up with the weeds--let alone his willful teen daughter and being short-staffed at the start of wedding season. Luckily, sunny counselor Gen Rockford could really use a summer job and a place for her girls to live. Now what began as the perfect solution for Gen and Caleb is transforming into one unforgettable summer. But will one little secret ruin it all?